Nilai Sosial dan Nilai Budaya pada Novel Filosofi Kopi Karya Dee Lestari serta Pemanfaatannya Sebagai Bahan Ajar di Kelas X SMA Negeri 1 Malingping - Maesaroh, Siti Imas (Universitas Mathla'ul Anwar Banten, 2022)
This study aims to describe the social and cultural values ​​in the Filosofi Kopi novel by Dee Lestari and the use of the Filosofi Kopi novel by Dee Lestari as a teaching material for learning to read novels in Class X SMA Negeri 1 Malingping. This study uses the type or research approach of Literature Studies. The steps used by researchers in collecting data are as follows: (1) outline the parts that are considered important, (2) select data, (3) provide a description, (4) draw conclusions. Sociological approach with content analysis strategy. The results of data analysis of social values ​​and cultural values ​​in the novel Filosofi Kopi by Dee Lestari and their use as teaching materials can be explained that the novel contains social and cultural values ​​and can be used as teaching materials in high school. The social values ​​found in the novel consist of 3 quotes of love. Empathy 5 quotes. Cooperation 2 quotes. Concern 3 quotes. Please help 3 quotes. Responsibilities 2 quotes. While the cultural values ​​found are honest 2 quotes. Hard work 5 quotes. Creative 2 quotes. Independent 2 quotes. Curiosity 3 quotes. As for the relevance to being used as teaching material, the novel is worthy of being taught in high school because: learning about values ​​in a novel is at the KD 5.1 high school level. Explains the intrinsic elements of reading fragments of the novel. As researchers and educators, efforts should be needed in teaching students to apply the values ​​contained in literary works in social life.